Dimensi Sosial Bazar Ramadan dalam Masyarakat Perkotaan: Studi Sosial Budaya di Perumahan Purwosari, Kecamatan Baturraden - Dwiki Darmawan; Rahman Latif Alfian (UIN Siber Syekh Nurjati Cirebon, 2025)
The Ramadan Bazaar in Purwosari Housing, Baturraden District, is a socio-cultural phenomenon that integrates economic, social, and cultural aspects within an urban community context. This study aims to analyze the social dimensions of the Ramadan Bazaar as a means of fulfilling economic needs, strengthening social bonds, and preserving traditional cultural values. The research employs a qualitative approach with descriptive-analytical and phenomenological methods, utilizing participatory observation and in-depth interviews with local residents. The findingsreveal that the Ramadan Bazaar not only assists underprivileged residents in accessing affordable basic necessities but also serves as a medium to enhance social cohesion through communal spirit and mutual cooperation. Furthermore, the event successfully blends modernity and tradition by adopting an efficient modern market model while maintaining cultural values such as solidarity and social care. The research findings highlight the significant role of the Ramadan Bazaar in fostering social cohesion, reducing economic disparities, and preserving cultural identity amidst modernization.